2023
DOI: 10.1002/mame.202300060
|View full text |Cite
|
Sign up to set email alerts
|

Additive Manufacturing‐Enabled Architected Nanocomposite Lattices Coated with Plasmonic Nanoparticles for Water Pollutants Detection

Sara Fateixa,
Marc Landauer,
Johannes Schneider
et al.

Abstract: Novel low‐cost materials to uptake and detect vestigial amounts of pesticides are highly desirable for water quality monitoring. Herein, are demonstrated, for the first time, surface‐enhanced Raman scattering (SERS) sensors enabled via additively manufactured lattices coated with plasmonic nanoparticles (NPs) for detecting pesticides in real water samples. The architected lattices comprising polypropylene (PP) and multiwall carbon nanotubes (MWCNTs) are realized via fused filament fabrication (FFF). In the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 77 publications
(113 reference statements)
0
8
0
Order By: Relevance
“…Although the proposed geometry is impractical for mold-based manufacturing, it is resolved by 3D printing. It is reported that the architectural geometry contributed to a higher sensitivity in terms of absorption behavior . Another application for a designed 3D printed device is the soft grippers used for food processing .…”
Section: D Printing Techniques In Fabricating Sensors and Actuatorsmentioning
confidence: 99%
See 4 more Smart Citations
“…Although the proposed geometry is impractical for mold-based manufacturing, it is resolved by 3D printing. It is reported that the architectural geometry contributed to a higher sensitivity in terms of absorption behavior . Another application for a designed 3D printed device is the soft grippers used for food processing .…”
Section: D Printing Techniques In Fabricating Sensors and Actuatorsmentioning
confidence: 99%
“…3D-printed carbon composites are prototyped as electrochemical sensors to detect pollutants in water. , The activated nanocarbon influences the voltammogram reading based on different pH variation. These sensors are manufactured by conductive polymer-based sensors by combination of direct ink writing (DIW) and FDM, or FDM alone. , The implementation of 3D printed pH sensors demonstrates promising results with excellent conductivity response in different pH concentrations ranging from 6.4 to 9. However, further improvements for temperature correction must be addressed to compete with commercially available sensors .…”
Section: D Printed Sensors For Food Quality Monitoring and Controlmentioning
confidence: 99%
See 3 more Smart Citations